The university of the future: A conceptual study in Malaysia - Mohd Hatta, Nur Amalina Maria; Nor Salleh, Izzati; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
The purpose of this research is to transform the current state of Universities into strategic initiatives that can utilize technology into University of the Future that lead to better development of the country. In this research, qualitative approach was selected involving the use of questionnaires distributed to the respondents. The sampling technique used in this research was simple random sampling where participants are chosen randomly by chance. This study was intended to answer two research questions. Firstly, do value proposition design (VPD) help to identify customer needs and wants from the University and secondly, how to transform the University of the Future using business model canvas (BMC). Based on the finding, the customer profile and the value map in VPD have help to identify and overcome problem faced. Besides, the information collected from VPD will be used to improve BMC to further improve the University of the Future. Thus, this study gave implications to design strategic initiatives for higher education especially Universities in using BMC and VPD and also to utilize the technology in this globalization era.